Analisa Penentuan Harga Jual Barang Produksi Menggunakan Metode Break Event Point (BEP) - Ribangun Bamban Jakaria; Afra Komang Prasetya; Syarif Rohmatdhoni; Wildan Nur Rahman (International Forum of Researchers and Lecturers, 2024)
The Break Even Point (BEP) analysis can be used by company management to determine product pricing, establish minimum sales, set sales targets, and plan desired profits. The objective of this research is to analyze the determination of the selling price of a production item using the Break Even Point (BEP) method. This research was conducted using a quantitative descriptive method through a cas study approach that employed Break Even Point (BEP) analysis calculations. The results of this research indicate that for the rice flour product of PT AMM, the Break Even Point (BEP) is reached at a sales amput of Rp. 2.129.816.330,-. At this break event point, the selling price of the product is determined to be Rp. 36,975,-, with a total quantity sold of 57,600 units. The sales level, with a variable expense ratio of 87%, allows the company to set the selling price of the product at the break even point (BEP) unit itself is 57.610 units that need to be sold. PT AMM has a profit target of Rp. 20.000.000,- must be made. This is because of the high variable costs; therefore, to achieve a high profit target, additional variable costs must be incurred.